Seismic attractor can assist in finding of geothermal area?. Issue 5 (3rd September 2018) - Smaglichenko, Tatyana A.; Smaglichenko, Alexander V.; Zelinka, Ivan; Chigarev, Boris
Abstract: The seismic active zone is a distributed system consisting of various subareas. To understand a state of the system during a given period of time so called 'the linear gradient frame' technique was developed to search the stable characteristics for subareas. The search is based on analysis of geographic components, least-squares inversion and statistical estimators of seismic data. The stable subarea includes hypocenters of earthquakes, the space-time trajectories of which are restricted by a certain domain (seismic attractor). Fractal structures obtained in south of Iceland are in an agreement with geological history. The results are promising for the geothermal exploration. Graphical Abstract: Diagram of the developed technique and demonstration of one from outcomes.